Types and Functions of Code Switching Found in TS Media Youtube Podcast with Naura Ayu - Priskawati, Putu; Sulatra, I Komang (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
Code switching is a common phenomenon in language use. When people have the ability to speak more than one language, they will combine the language and often switch the language. This study aims to find out the types of code switching found in Naura Ayu utterances in TS Media Podcasts and analyze the code switching functions found in Naura Ayu utterances in TS Media Podcasts. The data were taken from TS Media YouTube Podcast with Naura Ayu. Naura Ayu is one of famous singers in Indonesia and in her podcast she usually switches the code. This study used only one video among two videos. The data were collected from one video. The title of the video is TS Media Podcast with Naura Ayu Part 1 with the duration 28.34 minutes. The method used in analysing the data was qualitative method by applying several techniques, such as; watching, listening, finding the utterances with code switching, and taking notes. All of code switching types proposed by Poplack (1980) found in this study, those are inter-sentential switching, intra-sentential switching and tag switching.This study also found four functions of code switching among six functions proposed by Appel and Muysken (1987).Those functions are referential function, metalinguistic function, expressive function and directive function. The type of code switching that was dominant found in Naura Ayu utterances was intra-sentential switching, besides the dominant function of code switching found was referential function. Keywords: code switching, types, function, and podcast Alih kode merupakan fenomena umum dalam penggunaan bahasa. Ketika orang memiliki kemampuan untuk berbicara lebih dari satu bahasa, mereka akan menggabungkan bahasa dan sering beralih bahasa. Penelitian ini bertujuan untuk mengetahui jenis-jenis alih kode yang terdapat pada tuturan Naura Ayu dalam Podcast TS Media dan menganalisis fungsi alih kode yang terdapat pada tuturan Naura Ayu dalam Podcast TS Media. Data diambil dari TS Media YouTube Podcast bersama Naura Ayu. Naura Ayu adalah salah satu penyanyi terkenal di Indonesia dan dalam podcastnya dia biasanya mengganti kode. Penelitian ini hanya menggunakan satu video di antara dua video. Data dikumpulkan dari satu video. Judul videonya adalah TS Media Podcast dengan Naura Ayu Part 1 berdurasi 28.34 menit. Metode yang digunakan dalam menganalisis data adalah metode kualitatif dengan menerapkan beberapa teknik, seperti; mengamati, mendengarkan, menemukan ujaran dengan alih kode, dan mencatat. Semua jenis alih kode yang dikemukakan oleh Poplack (1980) ditemukan dalam penelitian ini, yaitu alih inter-sentential, alih intra-sentential, dan alih tag. Penelitian ini juga menemukan empat fungsi alih kode di antara enam fungsi yang dikemukakan oleh Appel dan Muysken (1987). Fungsi-fungsi tersebut adalah fungsi referensial, fungsi metalinguistik, fungsi ekspresif, dan fungsi direktif. Jenis alih kode yang dominan ditemukan pada tuturan Naura Ayu adalah alih kode intra-sentential, selain itu fungsi alih kode yang dominan ditemukan adalah fungsi referensial. Kata kunci: alih kode, tipe, fungsi, dan podcast